Kontrola regulowanej działalności gospodarczej jako płaszczyzna współdziałania organów samorządowych i przedsiębiorców - Łagowska, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The cooperation of a public and a private sector of economy is multifaceted and carried out by means of various activities. Local government has anumber of tasks important to the local community. Some of them also refer to the economic activity undertaken by private entities. Besides the classic law constructions, such as public-private partnership, cooperation also manifests itself in less typical forms. One of them will be acontrol, exercised by competent public authority of entrepreneurs performing aparticular type of economic activity recognized as regulated economic activity, inter alia at the stage of implementation of control recommendations applied to entrepreneurs. Given the extremely limited nature of control at the stage of undertaking regulated economic activity, exercising it along the activity is of great importance not only for both the entrepreneur and the controlling authority, but also for those whose needs the entrepreneur seeks to meet. Control activities should not be seen only as a sanction associated with the ability to limit, revoke permissions or the use of other administrative sanctions but also as aspecific kind of cooperation between controlling bodies and controlled entities to ensure legality of the activities. Indicated cases concern the work of the basic units of local government — municipalities. Moreover, the activities of running the nursery or children’s club and the collection of municipal waste from property owners are important from the point of view of residents and their needs of afundamental nature. Thus, this study focuses on the legal relationship at the control stage between the relevant local government bodies and entrepreneurs, operating in the field of municipal services by performing regulated economic activity.
Keywords: organy samorządu terytorialnego; przedsiębiorcy; współdziałanie; regulowana działalność gospodarcza; kontrola